Evidence of changing intrinsic water use efficiency under rising atmospheric CO 2 concentrations in Boreal Fennoscandia from subfossil leaves and tree ring δ 13 C ratios - Gagen, Mary; Finsinger, Walter; Wagner, Rike; McCarrol, Danny; Loader, Neil; Robertson, Iain; Jalkanen, Risto; Young, Giles H.F.; Kirchhefer, Andreas Joachim (Global Change Biology, 2010)
International audience Investigating the many internal feedbacks within the climate system is a vital component of the effort to quantify the full effects of future anthropogenic climate change. The stomatal apertures of plants tend to close and decrease in number under elevated CO 2 concentrations, increasing water use efficiency and reducing canopy evapotranspiration. Experimental and modelling studies reveal huge variations in these changes such that the warming associated with reduced evapotranspiration (known as physiological forcing) is neither well understood or constrained. Palaeo-observations of changes in stomatal response and plant water use efficiency under rising CO 2 might be used to better understand the processes underlying the physiological forcing feedback and to link measured changes in plant water use efficiency to a specific physiological change in stomata. Here we use time series of tree ring δ 13 C ( Pinus sylvestris ) and subfossil leaf ( Betula nana ) measurements of stomatal density and geometry to derive records of changes in intrinsic water use efficiency and maximum stomatal conductance in the Boreal zone of northern Finland and Sweden. We investigate the rate of change in both proxies, over the recent past. The two independent lines of evidence from these two different Boreal species indicate increased intrinsic water use efficiency and reduced maximum stomatal conductance of similar magnitude from pre-industrial times (ca. AD 1850) to around AD 1970. After this maximum stomatal conductance continues to decrease to AD 2000 in B. nana but intrinsic water use efficiency in i>P. sylvestris reaches a plateau. We suggest that northern boreal i>P. sylvestris might have reached a threshold in its ability to increase water use efficiency and we discuss the implication for modelling stomatal conductance in the land surface schemes of General Circulation Models.